2010
DOI: 10.1002/art.27497
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic brain connectivity in fibromyalgia is associated with chronic pain intensity

Abstract: Objective. Fibromyalgia (FM) is considered to be the prototypical central chronic pain syndrome and is associated with widespread pain that fluctuates spontaneously. Multiple studies have demonstrated altered brain activity in these patients. The objective of this study was to investigate the degree of connectivity between multiple brain networks in patients with FM, as well as how activity in these networks correlates with the level of spontaneous pain.Methods. Resting-state functional magnetic resonance imag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

54
538
2
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 561 publications
(596 citation statements)
references
References 72 publications
54
538
2
2
Order By: Relevance
“…These findings were consistent with previous evidence which supports the position that genuine acupuncture leads to stronger DMN deactivation than sham acupuncture on healthy subjects [44]. Previous resting-state fMRI studies have shown that various pain diseases were associated with abnormal connectivity patterns among DMN regions [45,46], and our research group confirmed that migraine patients without aura had a DMN abnormality compared with healthy controls [39]. The DMN has previously been suggested as a potential neural marker of treatment efficacy in chronic pain, and our findings demonstrated that active acupuncture analgesia could be achieved by regulating the migraineurs' resting state and changing the dysfunctional architecture of the DMN.…”
Section: The Difference In Resting-state Brain Activity Evoked By Actsupporting
confidence: 92%
“…These findings were consistent with previous evidence which supports the position that genuine acupuncture leads to stronger DMN deactivation than sham acupuncture on healthy subjects [44]. Previous resting-state fMRI studies have shown that various pain diseases were associated with abnormal connectivity patterns among DMN regions [45,46], and our research group confirmed that migraine patients without aura had a DMN abnormality compared with healthy controls [39]. The DMN has previously been suggested as a potential neural marker of treatment efficacy in chronic pain, and our findings demonstrated that active acupuncture analgesia could be achieved by regulating the migraineurs' resting state and changing the dysfunctional architecture of the DMN.…”
Section: The Difference In Resting-state Brain Activity Evoked By Actsupporting
confidence: 92%
“…For patients with lower pain level, it is possible that the sensorimotor cortex does not show pathophysiological modification or is less alerted when compared to patients with higher pain intensity. Indeed, several neuroimaging studies have demonstrated the correlation between pain intensity and degree of abnormal activity and connectivity within areas of the pain matrix in various chronic pain syndromes [60,64,65]. Future research to identify biomarkers and predictors of tDCS response could help to identify who and why some patients could benefit from this treatment, as well as to develop a patient-tailored stimulation protocol.…”
Section: Patients With Higher Pain Levels Seem To Respond Better To Tdcsmentioning
confidence: 99%
“…For instance, it has been shown that pain reduction induced by pregabalin intake was related to a decrease in connectivity between the default mode network (DMN) and the insular cortex [59], which is hyperactivated in patients with chronic pain [60,61]. In another neuroimaging study (i.e., functional MRI) evaluating the effects of M1 tDCS in patients with fibromyalgia, the authors demonstrated that tDCS induced a significant reduction in functional connectivity between the thalamus and the supplementary motor area, the medial prefrontal cortex and the cerebellum [62].…”
Section: How To Improve the Effects Of Tdcs?mentioning
confidence: 99%
“…However, the resulting descriptions of the function of the insula in such patients contain inconsistencies. For example, the insula (among other areas) had an increased connectivity to an organized set of areas known as the default mode network (DMN) at baseline in patients with chronic low back pain (Kornelsen et al, 2013; and in fibromyalgia (Napadow et al, 2010), whereas others found that insula to DMN connectivity at baseline was unchanged in complex regional pain syndrome (Bolwerk et al, 2013).…”
mentioning
confidence: 99%